Chlorhexidine: An elixir for periodontics - Arthiie Thangavelu; Sahaya Stelin Kaspar; Ramesh Periannan Kathirvelu; Bhuvaneshwari Srinivasan; Soundarya Srinivasan; Rajasekar Sundram (Wolters Kluwer Medknow Publications, 2020)
Chlorhexidine is a cationic bisbiguanide with broad antibacterial activity, and wide spectrum of activity encompassing gram-positive and gram-negative bacteria, yeasts, dermatophytes and some lipophilic viruses. Its antibacterial action is due to the disruption of the bacterial cell membrane by the chlorhexidine molecules, increasing the permeability and resulting in cell lysis. Thus, chlorhexidine plays a key role in the dentistry and is used to treat or prevent periodontal disease, and has earned its eponym of the gold standard. This article reviews in detail about the mechanism of action, indications, forms and various studies related to chlorhexidine.